METHOD OF PREVENTING PURULENT-SEPTIC COMPLICATIONS OF LIVER ECHINOCOCCOSIS (World Bulletin of Public Health, 2024)
The literature and our own data on modern methods of surgical treatment and clinical and immunologically based methods for choosing the prevention of purulent-septic complications in patients with liver echinococcosis , corresponding to the principles of evidence-based medicine, are summarized. Along with this, new algorithms for diagnostic and treatment tactics for uncomplicated and complicated forms of hydatid echinococcosis of the liver are described in detail.
Keywords: Echinococcosis; liver; immunity